Performance evaluation of heat transfer enhancement for internal flow based on exergy analysis. (12th September 2007) - Abdel-Moneim, S.A.; Ali, R.K.
A performance evaluation based on exergy analysis was proposed to evaluate the benefits of different enhancement techniques for flow inside tubes. The present performance evaluation was developed based on the application of the principle of entropy generation. A semi-analytical model was developed to predict the entropy generation and the exergy destruction rates associated with both flow friction and heat transfer. This model was based on measurements and empirical correlations for both flow and heat transfer characteristics. The present performance evaluation was applied on flow through tubes enhanced with twisted-tapes inserts, spirally internal fins and conical turbulators for three different fluids. It was found that using specific types of enhancement techniques reduces the irreversibility owing to heat transfer across a finite temperature difference and in the same time increases that part of irreversibility resulting from the flow friction. Therefore, a thermodynamic optimum at a minimum exergy destruction rate can be achieved for different enhancement techniques and different flow conditions.